Silicon-carbon negative electrode material, preparation method thereof, negative electrode slurry, negative electrode plate and application

By adding polycarbonsilane to the silicon carbon negative electrode material to form a 3D network structure, the problem of high impedance and insufficient strength of silicon carbon materials is solved, the high energy density and long life of the material are achieved, the graphitization process is delayed, and the resistance is enhanced The pressure strength improves battery performance.

CN119133417APending Publication Date: 2024-12-13NINGBO SHANSHAN SILICON-BASED MATERIALS CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411546177.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing silicon carbon negative electrode materials are difficult to effectively apply in batteries due to the high impedance of linear phenolic resin-based activated carbon and the poor toughness caused by the strength of carbon materials. Especially under high pressure conditions, the material is prone to expand, affecting the battery life.

Method used

Polycarbonsilane is incorporated into linear phenolic resin of polymer materials to generate SICs, form a 3D network structure, improve the mesoporous ratio, delay the graphitization process, enhance the compressive strength of the material, and prepare porous carbon skeletons through spray drying, carbonization and activation processes , combined with silane and acetylene precipitation, form a silicon carbon negative electrode material.

Benefits of technology

The circulation retention rate and battery life of silicon carbon negative electrode materials are improved, the compressive strength of the material is enhanced, the lithium embedded expansion is reduced, and the energy density and electrochemical performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133417A_ABST
    Figure CN119133417A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-carbon negative electrode material, a preparation method thereof, negative electrode slurry, a negative electrode plate and application. The invention provides a preparation method of a silicon-carbon negative electrode material, which comprises the following steps: S1, mixing linear phenolic resin with an organic solvent, sequentially adding urotropine, carbon nanotubes, a defoaming agent and polycarbosilane, and mixing to form a mixture; s2, drying, cross-linking, carbonizing, activating and cooling the mixture to obtain a porous carbon material; s3, silane mixed gas is introduced into the porous carbon material, silane deposited porous carbon is obtained through deposition, then acetylene mixed gas is introduced, nitrogen is introduced after acetylene deposition, and the silicon-carbon negative electrode material is obtained through cooling; wherein the polycarbosilane is a compound as shown in a formula I, and n ranges from 1000 to 2000. According to the negative electrode material prepared by the method, the mesoporous strength is improved, the expansion coefficient is reduced, the cycle retention rate of the battery is improved, and the service life of the battery is prolonged. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon negative electrode material, a preparation method thereof, a negative electrode slurry, a negative electrode pole piece and applications thereof. Background Art

[0002] Silicon carbon negative electrode has a very high gram capacity of 1900mah -1 (0.8v), its higher lithium insertion potential is 0.4V (Li\Li + ) can also inhibit lithium dendrites. Although the overall discharge platform will be reduced by about 0.1v, due to its extremely high gram capacity, a trace amount of doping can increase the gram capacity of traditional negative electrode materials, which has attracted much attention in the new energy industry. Limited by the slow growth of the overall positive electrode gram capacity and high impedance, the actual amount of lithium dragged is severely limited by the voltage of the battery. However, under high voltage conditions, the oxygen in the positive electrode material is easy to escape. And in the existing consumer battery electrolytes, because carbonates have the advantages of high dielectric constant and high boiling point, it is difficult to be replaced by other mainstream solvents and additives in a short period of time, and carbonates have the disadvantage of a small voltage window. Therefore, improving the gram capacity of negative electrode materials has become the mainstream industry direction. This has led to negative electrode silicon-carbon materials being one of the hot directions in the new energy industry. Data show that 5% doping of silicon-carbon negative electrode can make the theoretical gram capacity of 372mahg -1 The graphite negative electrode achieves actual 420mahg -1 8% silicon carbon doping can achieve 450mahg -1 , 10% silicon carbon doping can achieve 480whL -1 In addition, because silicon has a higher density, its compaction density is much greater than that of graphite under the same pressure, making 800whL -1 The volume energy density can be achieved, with a volume energy density of 500whL -1 Compared with the graphite negative electrode battery, the capacity of lithium-ion batteries with the same volume or mass is still close to 600whL even if the battery with silicon-carbon negative electrode material fails (defined as 80% SOC). -1 , still greater than graphite. It can be said that silicon negative electrode batteries have many huge advantages over traditional graphite negative electrode batteries in terms of energy density and cycle performance. Amorphous silicon carbon prepared by silane precipitation has a higher initial efficiency and has outstanding advantages over nano silicon prepared by grinding. It is currently the most popular direction in the industry's energy 3C field. The negative electrode silicon carbon technology of silane precipitation of amorphous nano silicon-subnano silicon is undoubtedly a lever to push the battery volume energy density to 1000whL -1 As a powerful lever, the emergence of silicon-carbon negative electrode materials has also enabled the energy density of the overall battery industry to increase from 3% per year to 5% per year.

[0003] However, the preparation mechanism of porous carbon is often limited by the activation treatment of carbon materials, which leads to the fact that the generated porous carbon is often limited by the precursor and sintering activation process. Therefore, the strength of the prepared porous carbon is often not high. There are many main reasons, including the physical structure and chemical composition of void distribution, hybridization mode of carbon materials, degree of graphitization of carbon materials, etc. Although the strength of silicon-carbon materials will be improved after silane precipitation and acetylene gas coating, there are still great limitations in practical applications. For example, silicon-carbon materials with high strength have large expansion and weak release times, while silicon-carbon materials with low strength have small expansion and strong release times. Therefore, the current preparation of silicon-carbon actually has many contradictions. How to balance these contradictions will be an important direction for silicon-carbon materials to be fully applied from energy storage in the 3C power industry.

[0004] Nowadays, in order to solve the basic problems of weak discharge times of silicon-carbon batteries, low material strength and difficulty in processing, and short battery life caused by high lithium expansion, a variety of solutions have been adopted, such as using different precursors, repeatedly making various improvements in asphalt, phenolic resin, and biomass precursors to improve the overall practical performance of activated carbon, and improving silane precipitation by changing silane precipitation technology, including improvements in sintering furnaces, types and methods of gas precipitation, and precipitation temperature curves. However, it cannot alleviate the problem of high impedance of phenolic resin-based activated carbon itself, high overall strength of carbon materials, and poor toughness. Summary of the invention

[0005] The technical problem to be solved by the present invention is to overcome the problem that the silicon-carbon negative electrode material in the prior art cannot alleviate the problem that the linear phenolic resin-based activated carbon has a high impedance and the overall strength of the carbon material is high, resulting in poor toughness. The present invention provides a silicon-carbon negative electrode material, a preparation method thereof, a negative electrode slurry, a negative electrode plate and its application. By adding a polymer material polycarbosilane to the polymer material linear phenolic resin, the solid content of the precursor is increased as much as possible, SIC is generated, a 3D network structure is generated, the ratio of the mesopores of the material to provide empty volume is increased, the lithium insertion expansion of the plate in the first cycle is reduced, and the process of graphitization formation of the negative electrode material is delayed so that the activated carbon develops into amorphous carbon. Based on the low lithium insertion expansion of hard carbon, the cycle retention rate of the battery is improved, and the generated β-silicon carbide enhances the compressive strength of the negative electrode material, which is beneficial for the preparation of high energy density batteries and increases the life of the battery.

[0006] The present invention solves the above technical problems through the following technical solutions:

[0007] The present invention provides a method for preparing a silicon-carbon negative electrode material, which comprises the following steps:

[0008] S1: after mixing the linear phenolic resin with the organic solvent, hexamethylenetetramine, carbon nanotubes (CNT), a defoaming agent and polycarbosilane are added in sequence to obtain a mixture;

[0009] S2: spray drying the mixture to obtain a particle, and then carbonizing and activating the particle to obtain a porous carbon skeleton;

[0010] S3: depositing the porous carbon skeleton under a silane mixed gas to form a core body, then precipitating under an acetylene mixed gas, and finally depositing under a nitrogen atmosphere to obtain a silicon-carbon negative electrode material;

[0011] Wherein, the polycarbosilane is a compound as shown in Formula I,

[0012] ,

[0013] Among them, n is 1000~2000.

[0014] In one embodiment, n is 1500.

[0015] In one embodiment, in step S1, the organic solvent is an alcohol solvent, preferably ethanol.

[0016] In one embodiment, in step S1, the mass ratio of the linear phenolic resin to the organic solvent is 1:(1-3), for example, 1:2.

[0017] In one embodiment, in step S1, the mixture includes 80-120 parts of linear phenolic resin, 4-7 parts of urotropine, 0.05-0.2 parts of carbon nanotubes, 0.05-0.2 parts of defoaming agent and 0.05-0.5 parts of polycarbosilane, wherein the parts are the mass fractions of the substances in the total components.

[0018] In one embodiment, in step S1, the mixture includes 100 parts of linear phenolic resin, 6 parts of urotropine, 0.1 parts of carbon nanotubes, 0.1 parts of defoaming agent and (0.1-0.4) parts of polycarbosilane, wherein the parts are the mass fractions of the substance in the total components.

[0019] In one embodiment, in step S1, the weight fraction of the polycarbosilane is 0.1, 0.2, 0.3 or 0.4, for example, 0.2, 0.3 or 0.4.

[0020] In a certain embodiment, in step S1, the mixture consists of linear phenolic resin, urotropine, carbon nanotubes, a defoamer and polycarbosilane. Preferably, the mixture consists of 80-120 parts of linear phenolic resin, 4-7 parts of urotropine, 0.05-0.2 parts of carbon nanotubes, 0.05-0.2 parts of defoamer and 0.05-0.5 parts of polycarbosilane; for example, the mixture consists of 100 parts of linear phenolic resin, 6 parts of urotropine, 0.1 parts of carbon nanotubes, 0.1 parts of defoamer and 0.2 parts of polycarbosilane.

[0021] The defoamer is a conventional defoamer in the art, such as a silicone polyether defoamer.

[0022] In one embodiment, in step S1, the mixing is performed by ball milling with a homogenizer.

[0023] In one embodiment, in step S1, the rotation speed of the ball milling mixing is 1000-3000 r / min, for example, 2000 r / min.

[0024] In one embodiment, in step S1, the ball milling mixing time is 50 to 80 minutes, for example, 60 minutes.

[0025] In one embodiment, in step S2, the spray drying temperature is 100-150°C, for example, 130°C.

[0026] In one embodiment, in step S2, the carbonization operation includes placing the spray-dried particles in a rotary furnace for cross-linking.

[0027] In one embodiment, in step S2, the carbonization temperature is 1200-1800°C, for example, 1200°C, 1600°C or 1800°C, preferably 1600°C.

[0028] In one embodiment, in step S2, the carbonization is carried out in an inert atmosphere, preferably in a nitrogen atmosphere; the nitrogen supply rate is 0.5-1.5 L·kg -1 min -1 , for example 1L kg -1 min -1 .

[0029] In one embodiment, in step S2, the carbonization needs to be carried out at a higher temperature, wherein the heating process is divided into two stages:

[0030] Stage 1: Heating rate is 3~6℃ / min, for example 4℃ / min; Heating time is 50min; Heating to 200℃ and keeping for 1h;

[0031] The second stage: the heating rate is 4°C / min, and the heating time is 250-400min.

[0032] In one embodiment, in step S2, the high temperature in the first stage of carbonization causes cross-linking of the polycarbosilane.

[0033] In a certain embodiment, in step S2, the activation operation is preferably performed by introducing an activation medium to perform pore-forming treatment.

[0034] In one embodiment, in step S2, the activation medium is carbon dioxide; wherein the gas supply rate of the activation medium carbon dioxide is 1-3 L·kg-1 min -1 , for example 2L·kg -1 min -1 .

[0035] In one embodiment, in step S2, the activation temperature is 600-1100°C, for example, 550°C.

[0036] In one embodiment, in step S2, the activation time is 1 to 10 hours, for example, 9 hours.

[0037] In one embodiment, in step S2, the activation preferably includes a cooling step, wherein the cooling is performed by cooling the furnace temperature to 400-600°C, for example, to 550°C.

[0038] In the present invention, in step S3, the silane mixed gas may be a mixed gas of conventional silane and inert gas in the art, and the silane is preferably SiH4.

[0039] In one embodiment, in step S3, the silane mixed gas is 20% silane and 80% argon, preferably 20% SiH4 and 80% argon, wherein the ventilation volume of the mixed gas is 10-20 L·kg -1 min -1 , for example 15L·kg -1 min -1 .

[0040] In one embodiment, in step S3, the temperature of the silane deposition is 450-550°C, for example, 550°C.

[0041] In one embodiment, in step S3, the silane deposition time is 8 to 12 hours, for example, 10 hours.

[0042] In one embodiment, in step S3, the acetylene mixed gas is 20% acetylene and 80% argon by mass percentage; wherein the ventilation volume of the mixed gas is 4-8 L·kg -1 min -1 , for example 5L·kg -1 min -1 .

[0043] In one embodiment, in step S3, the temperature of the acetylene deposition is 450-550°C, for example, 500°C.

[0044] In one embodiment, in step S3, the acetylene deposition time is 8 to 12 hours, for example, 10 hours.

[0045] In one embodiment, in step S3, after the acetylene deposition, a cooling operation is also included, wherein the temperature is lowered to room temperature.

[0046] The present invention also provides a silicon-carbon negative electrode material prepared by the above preparation method.

[0047] In one embodiment, the mass percentage of the polycarbosilane in the silicon-carbon negative electrode material is 0.09% to 0.4%.

[0048] In one embodiment, the residual SIC in the silicon-carbon negative electrode material is 0.1% to 5%, preferably 0.8% to 3.6%, and more preferably 1.8% to 3.6%.

[0049] In one embodiment, the spray-dried particles have a diameter of 7 to 9 μm, preferably 7.4 to 8.3 μm.

[0050] In a certain embodiment, the residual carbon rate in the silicon-carbon negative electrode material (ie, the carbon content in the silicon-carbon negative electrode material / the mass % of the phenolic resin) is 50-70%, preferably 52.4-58.7%.

[0051] In one embodiment, the true density of the silicon-carbon negative electrode material after carbonization is 2.0~2.8 g / cm³, preferably 2.69~2.79 g / cm³.

[0052] In one embodiment, the particle size (D50) of the silicon-carbon negative electrode material at 20 MPa is 5-9 μm, preferably 5.6-8.7 μm, and more preferably 7.5-8.7 μm.

[0053] In one embodiment, the BET of the silicon-carbon negative electrode material is 1500-1800 m -2 g, preferably 1603.9~1780.1 m -2 g.

[0054] In one embodiment, the ratio of the empty volume provided by the mesopores of the silicon-carbon negative electrode material is 12-20%, preferably 12.9-16.7%.

[0055] In one embodiment, the first cycle expansion of the full battery of the silicon-carbon negative electrode material is 80-98%, for example, 89-94%.

[0056] In one embodiment, the first efficiency of the full battery of the silicon-carbon negative electrode material is 82-90%, preferably 82.2-87.8%.

[0057] The present invention also provides a negative electrode slurry, which comprises the silicon-carbon negative electrode material as described above, a conductive agent, a binder and a solvent.

[0058] In the present invention, the conductive agent and the binder are conventional conductive agents and binders in the art.

[0059] In a certain embodiment, the conductive agent may be acetylene black (Super P).

[0060] In a certain embodiment, the binder may be polyacrylic acid (PAA).

[0061] In one embodiment, the solvent may be water, which serves as a dispersant to form a slurry.

[0062] In a certain embodiment, the solid content of the negative electrode slurry may be 0.1-1 wt %.

[0063] The present invention provides a negative electrode plate, which is made by using the negative electrode slurry as described above.

[0064] In a certain embodiment, the method for preparing the negative electrode sheet may include: coating the negative electrode slurry on a current collector and baking the negative electrode slurry.

[0065] In a certain aspect, the coating may be a single-sided coating.

[0066] In one embodiment, during the coating, the active material is coated to a thickness of 40 μm.

[0067] In a certain embodiment, during the coating, the coating speed is 40 cm / s.

[0068] In a certain embodiment, the current collector may be a copper foil, and the thickness of the copper foil may be 8-10 μm.

[0069] In one embodiment, the baking temperature is 50°C-130°C.

[0070] In a certain embodiment, the baking time is 400s.

[0071] The present invention also provides an application of the silicon-carbon negative electrode material as described above in a battery, wherein the application includes preparing a negative electrode sheet of the battery with the silicon-carbon negative electrode material.

[0072] In one embodiment, the battery is a lithium-ion battery.

[0073] In one embodiment, the mass fraction of the silicon-carbon negative electrode material in the negative electrode plate is 5-10%, for example, 8%.

[0074] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0075] The reagents and raw materials used in the present invention are commercially available.

[0076] The positive and progressive effects of the present invention are:

[0077] (1) By adding polycarbosilane to the silicon-carbon negative electrode material to generate SIC, a 3D network structure is generated, the ratio of the mesopores of the material to provide empty space is increased, and during the activation process, CO2 activation gas is more easily able to enter and activate the carbon material;

[0078] (2) As the content of trace polycarbosilane increases, the ohmic resistance of the silicon-carbon material does not increase sharply, effectively improving the strength of the matrix while maintaining the low internal resistance of graphite-like carbon;

[0079] (3) By adding polycarbosilane to the silicon-carbon negative electrode material, the graphitization process of the silicon-carbon negative electrode material can be delayed, and the expansion of the first cycle of the pole piece embedded with lithium is also reduced, thereby improving the cycle retention rate of the battery and increasing the battery life;

[0080] (4) By adding polycarbosilane to the silicon-carbon negative electrode material and sintering it at a suitable temperature to generate β-silicon carbide, the generated silicon carbide is on the surface of the mesopore wall, thereby enhancing the compressive strength of the silicon-carbon negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0081] Figure 1 It is the structure of silicon-carbon negative electrode material generated by carbonization without adding polycarbosilane;

[0082] Figure 2 The structure of silicon-carbon negative electrode material is generated by carbonization by adding polycarbosilane. DETAILED DESCRIPTION

[0083] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0084] Abbreviation table

[0085]

[0086] Example 1 Preparation of silicon-carbon negative electrode material

[0087] 1 kg of linear phenolic resin (RF) was mixed with 2 kg of ethanol at a mass ratio of 1:2, and then hexamethylenetetramine (HMT), CNT, silicone polyether defoamer, and polycarbosilane were added in sequence. The mixture was mixed according to the weight ratio (recorded in Table 1), mixed by a high-speed disperser homogenizer, and the ball mill speed was 2000r / min for 60min. It was spray-dried at 130°C to a particle diameter of 8μm. The spray-dried particles were placed in a rotary furnace for cross-linking first and then carbonization. The front temperature rise curve was 4°C / min, the temperature was raised for 50min, and then raised to 200°C for 1h. The main purpose was to cross-link the polycarbosilane. The rear temperature rise curve was 4°C / min, the temperature was raised for 250min, (to 1200°C), nitrogen atmosphere protection, and the nitrogen gas supply rate was 1L·kg -1 min -1 After activation for 9 h in a CO2 atmosphere, a porous carbon skeleton was obtained. The CO2 gas supply rate was 2 L·kg -1 min -1 After cooling to a furnace temperature of 550°C, the atmosphere was switched to a silane mixture (20% SiH4 and 80% argon by mass), and the core was formed by deposition at 500°C for 10 h with a ventilation volume of 15 L kg -1 min -1 Then switch the atmosphere to an acetylene mixture (20% acetylene and 80% argon by mass), with a ventilation volume of 5 L kg -1 min -1 , continue to deposit at 500°C for 10 hours, then switch to nitrogen, and then cool to room temperature 25°C to obtain a silicon-carbon negative electrode material.

[0088] Among them, the structure of polycarbosilane is , n is 1500.

[0089] Table 1 Main process parameters

[0090]

[0091] Example 2 Performance Test

[0092] 2.1 Test of particle size (D50) of spray-dried particles, activated porous carbon skeleton, and prepared silicon-carbon negative electrode material at 0MP and 20MP

[0093] The particle sizes (D50) of the spray-dried particles, the activated porous carbon skeleton, and the prepared silicon-carbon negative electrode material at 0MP and 20MP in the preparation process of Example 1 were tested respectively, and the test results are shown in Table 2. The particle size measurement in this test was carried out using a Masterizer-2000 laser particle size analyzer.

[0094] Table 2 Test table of particle size (D50) of spray-dried particles, activated porous carbon skeleton, and prepared silicon-carbon negative electrode material at 0MP and 20MP

[0095]

[0096] It can be seen from the particle size change at 0MPa and 20MPa that the particle size (D50) of the prepared silicon-carbon negative electrode material is equivalent to the particle size (D50) at 20MPa, which indicates that the silicon-carbon negative electrode material prepared above has low strength and will break under high pressure conditions, making the particle size smaller.

[0097] 2.2 Performance tests of residual carbon rate, SIC residual amount, activated carbon rate, core silane deposition rate, BET and mesopore provided void volume ratio

[0098] During the preparation process of Example 1, the residual carbon rate of the porous carbon skeleton obtained by the prepared mixture before and after carbonization, the SIC residual amount of the porous carbon skeleton obtained by the prepared mixture before and after carbonization, the silane deposition rate of the prepared core, the specific surface area (BET) of the silicon-carbon negative electrode material, and the ratio of the empty volume provided by the mesopores of the silicon-carbon negative electrode material were tested respectively.

[0099] The test results are shown in Table 3, where the residual carbon rate (%) = the mass of the prepared mixture before carbonization / the mass of the porous carbon skeleton obtained after carbonization;

[0100] The residual SIC is the residual amount of SIC after carbonization. It was tested by Thermo K-Alpha. After taking 0.1g sample, full spectrum and fine spectrum scanning tests were performed respectively. The phase was tested based on the full spectrum, and quantitative scanning was performed based on the fine spectrum. After fitting with Avantage, quantification was performed.

[0101] Activated carbon rate test = activated carbon mass / precursor mass (i.e. carbon content of silicon-carbon negative electrode / phenolic resin mass);

[0102] Core silane deposition rate = mass of silicon deposited on the core / mass of silane introduced;

[0103] BET test and mesopore test are performed using Micromeritics' ASAP2020.

[0104] Table 3 Performance tests of residual carbon rate, SIC residual amount, activated carbon rate, core silane deposition rate, BET and ratio of mesopore provided void volume

[0105]

[0106] According to the above table, after adding polycarbosilane, the ratio of the empty volume provided by the mesopores of the prepared silicon-carbon is significantly improved, and the SIC value of the prepared silicon-carbon negative electrode material will be improved, which promotes the activation of the silicon-carbon negative electrode material.

[0107] 2.3 True density of porous carbon skeleton and density test of silicon-carbon negative electrode material

[0108] The true density measurement method in the embodiment adopts ULTRA1000 true density meter test results are shown in Table 4.

[0109] Table 4 True density of porous carbon skeleton and density test of silicon-carbon negative electrode material

[0110]

[0111] Example 3 Full battery test of negative electrode materials

[0112] Preparation of negative electrode slurry and pole piece: Mix the negative electrode formula CMC:PAA:SBR:SP:CNTs:silicon carbon:graphite = 0.5:3.5:0.5:1:0.1:8:86.4, and add DMAP with different negative electrode solid content ratios (0.1%-1%) to the slurry. The order of adding materials for the preparation of negative electrode slurry is graphite→CMC→SP→CNT→DMAP, and then disperse it for 3 hours with a planetary disperser with a rotation speed of 300r / min and a revolution of 1000r / min, inject 80% deionized water at a time, rotate at 500r / min, and rotate at 600r / min for 1 hour, add PAA, rotate at 500r / min, and rotate at 500r / min for 1 hour, and finally add SBR, rotate at 300r / min and rotate at 300r / min for 1 hour, and obtain the current collector to be coated. The coated current collector uses 8μm thick copper foil, coated on one side, with the coated side facing the negative electrode of the button battery, and the thickness of the active material coated on one side is 40μm, with a compaction density of 1.7g / cm 3 The coating speed is 40 cm / s, the post-baking temperature is 50°C-130°C, and the drying time is 400s.

[0113] Battery electrolyte formula: EC 20%, PC 20%, DEC 20%, PP 15%, LiPF6 15%, FEC 6%, PS 2.5%, LiODFB 1.5%, wherein the percentage content is the mass percentage content of each component in the total formula. The substances in the above formula are mixed to obtain an electrolyte.

[0114] About 0.5 ml of the electrolyte of the above formula was added to the button cell, and the entire battery was assembled in a glove box to avoid contact with air.

[0115] Half-cell preparation: CR2450 button cell was used for testing, with a single negative electrode sheet as the positive electrode and a lithium sheet as the negative electrode.

[0116] The silicon-carbon negative electrode material prepared in Example 1 was prepared as described above to obtain a battery, and its resistivity at 0MPa and 20MPa, the silicon content of the whole battery, and the battery capacity were tested. The test was conducted using the Xinwei CT-4008Q-5V6A. The first efficiency was determined by dividing the discharge capacity of the first cycle / the charge capacity, and the fast charge capacity retention rate was the discharge capacity of the newly formed button battery / the discharge capacity of the newly formed button battery at 0.1C. The capacity retention rate was the capacity discharged after the cycle / the capacity discharged in the first cycle.

[0117] The test results are shown in Table 5.

[0118] Table 5 Battery electrical test

[0119]

[0120] According to Table 5, after adding polycarbosilane, the lithium expansion of the battery will be reduced; the data of 10-cycle cycle retention rate show that under extremely high pressure and density conditions, although the pore volume provided by the mesopores of the silicon-carbon negative electrode material is improved, the strength is not reduced. Analyzing its principle, it is due to the reasonable sintering temperature that β-silicon carbide is generated. At the same time, the generated silicon carbide enhances the compressive strength on the surface of the mesopore wall. It is generally believed that silicon-carbon materials with low strength can be broken at a compaction density of 1.70, and the broken silicon-carbon will greatly reduce the life of the battery. The silicon-carbon prepared in the embodiment of the present application has a higher life, which shows that polycarbosilane can enhance the strength of the mesopores.

[0121] It can be seen from the resistivity at 0MPa and 20MPa that it will produce a mutation effect.

[0122] It can be clearly seen from the above data that trace amounts of polycarbosilane doping and calcination at different temperatures show variable data trends. Reasonable doping of polycarbosilane and appropriate calcination temperature significantly enhance the overall circulation degree of the material at the battery end, indicating that trace amounts of silicon carbide are extremely beneficial for silicon-carbon materials to maintain their original structure under high pressure.

[0123] in conclusion

[0124] 1. The influence of different contents of polycarbosilane at the same temperature.

[0125] Polycarbosilane generates SIC during the carbonization process, producing a 3D network structure such as Figure 2 As shown (wherein, the negative electrode material produced without adding polycarbosilane is as follows Figure 1 As shown. ), while generating mesopores, solid or thin-walled linear structures in block or linear form are formed, which have an activation effect when the specific surface area is not high. However, when the content is further increased, due to its stable structure, it will affect the activation of the carbon material and reduce the specific surface area of ​​the carbon skeleton. The activation effect is mainly to form mesopores. For example, in Examples 1 to 4, the pore volume ratio of the mesopores has not been greatly reduced with the addition of polycarbosilane. This shows that the mesopores formed during the carbonization process are beneficial to the activation process. The CO2 activation gas can more easily enter and activate the silicon-carbon material.

[0126] In addition, it can be seen that as the polycarbon silicon content increases, the ohmic resistance of the silicon-carbon material increases and the conductivity decreases. The increase in ohmic resistance is mainly due to two reasons. One is that the resistivity of silicon carbide is greater than that of carbon materials. The other is that the increase in the proportion of mesopores leads to a decrease in the overall density. Among them, because the proportion of silicon carbide is extremely low, the resistivity of the material is still mainly due to the change in the overall density of the carbon material.

[0127] In addition, polycarbosilane itself has flame retardant properties, increases the residual carbon rate, and delays the process of carbon graphitization. This is also the reason why the resistance of SIC-containing materials is relatively high.

[0128] 2. The effect of polycarbosilane addition on carbon skeleton strength at the same temperature.

[0129] With the increase of polycarbosilane, the SIC content in the carbon skeleton changes from 0.8% to 3.6%. Under a pressure of 20 MPa, the compaction density of the material gradually decreases with the increase of SIC content, and the particle size change under pressure is no longer obvious. The effect is shown in Examples 5-8.

[0130] In addition, with the increase in carbon skeleton strength, the expansion of lithium embedded in the first cycle of the electrode has also decreased, which has also improved the cycle retention rate. With the increase in SIC content, the resistivity of the electrode has increased, which makes the internal resistance of the battery cell itself larger. Therefore, the overall discharge performance of the battery has a trend of first increasing and then decreasing, which is more obvious in the 0.2C discharge retention rate of Example 5 and Example 8.

[0131] 3. The electrochemical performance of polycarbosilane with the same content is different at different temperatures.

[0132] As the sintering temperature increases, it can be seen that sintering at 1600℃ is more advantageous than sintering at 1200℃ and 1800℃. The main reason is that polycarbosilane will not crystallize until it is above 1200℃, and it is mostly amorphous below 1200℃. When polycarbosilane produces crystalline SIC, it first produces β-SIC, also known as cubic silicon carbide, at a lower temperature, and then transforms into α-SIC. Compared with the two, the former has higher strength and conductivity. α-SIC usually transforms at 1600℃. In addition, although linear phenolic resin is a hard carbon material, it will also transform into graphitization at high temperature. With the high temperature dehydrogenation, SP 3 CH to SP 2 CC transformation, as the strength becomes lower, coupled with the mutual aggregation of carbon atoms, macropores and slit-shaped mesopores appear in the silicon-carbon material, which leads to the overall pressure resistance of the silicon-carbon material, which is manifested in the poor performance of the battery. From the data, it can be seen that its appropriate activation has an effect on 1800 m- 2 The parameters below g play a certain role in boosting. When the temperature is too high, the crystallinity increases, the grains grow larger and aggregate, and the polycarbosilane is too high, resulting in the agglomeration of SIC, which will hinder the activation of the activator. Because of the change in the specific surface, it will also affect the subsequent silane precipitation and the specific performance of short battery life.

[0133] The main manifestation is that when the specific surface area decreases, the silane deposition amount becomes lower, the silane precipitation is uneven, resulting in a decrease in the gram capacity of silicon carbon, and also reducing the first efficiency, cycle and discharge of the battery, and also affecting the expansion of the pole piece. This can be seen at lower temperatures, such as Examples 1-4, and higher temperatures, such as Examples 9-12, under the same formula. It can also be seen in Examples 1, 5, and 9 that under the same formula, the higher the temperature, the lower the powder resistivity.

[0134] In summary, under the coordination of sintering temperature and the amount of polycarbosilane added, the prepared negative electrode material has a significant effect on improving battery performance.

Claims

1. A method for preparing a silicon-carbon negative electrode material, comprising the following steps: S1: after mixing a linear phenolic resin with an organic solvent, hexamethylenetetramine, carbon nanotubes, a defoaming agent, and polycarbosilane are sequentially added to obtain a mixture; S2: spray drying the mixture to obtain a particle, and then carbonizing and activating the particle to obtain a porous carbon skeleton; S3: depositing the porous carbon skeleton under a silane mixed gas to form a core body, then depositing it under an acetylene mixed gas, and finally depositing it under a nitrogen atmosphere to obtain a silicon-carbon negative electrode material; in, The polycarbosilane is a compound as shown in Formula I, , Among them, n is 1000~2000.

2. The method for preparing the silicon-carbon negative electrode material according to claim 1, characterized in that: It meets one or more of the following conditions: (1) n is 1500; (2) In step S1, the organic solvent is an alcohol solvent, preferably ethanol; (3) In step S1, the mass ratio of the linear phenolic resin to the organic solvent is 1:(1-3), for example, 1:2; (4) In step S1, the mixture includes 80-120 parts of linear phenolic resin, 4-7 parts of urotropine, 0.05-0.2 parts of carbon nanotubes, 0.05-0.2 parts of defoaming agent and 0.05-0.5 parts of polycarbosilane, wherein the parts are the mass fractions of the substances in the total components; Preferably, the mixture comprises 100 parts of linear phenolic resin, 6 parts of urotropine, 0.1 parts of carbon nanotubes, 0.1 parts of defoaming agent and 0.1-0.4 parts of polycarbosilane, wherein the parts are the mass fractions of the substance in the total components, and preferably, the weight fraction of the polycarbosilane is 0.1, 0.2, 0.3 or 0.4, for example, 0.2, 0.3 or 0.4; (5) The defoaming agent is a silicone polyether defoaming agent; (6) In step S1, the mixing is performed by ball milling with a homogenizer; (7) In step S2, the spray drying temperature is 100-150°C, for example, 130°C; (8) In step S2, the carbonization operation includes placing the spray-dried particles in a rotary furnace for cross-linking; (9) In step S2, the carbonization temperature is 1200-1800°C, for example, 1200°C, 1600°C or 1800°C, preferably 1600°C; (10) In step S2, the carbonization is carried out in an inert atmosphere, preferably in a nitrogen atmosphere; the nitrogen supply rate is 0.5-1.5 L·kg -1 min -1 , for example 1L kg -1 min -1 ; (11) In step S2, the carbonization needs to be carried out at a high temperature, wherein the heating process is divided into two stages: The first stage: the heating rate is 3~6℃ / min, for example 4℃ / min; the heating time is 50min; the temperature is raised to 200℃ and kept for 1h. The second stage: the heating rate is 4℃ / min, and the heating time is 250-400min; (12) In step S2, the activation operation is to introduce an activation medium to perform pore-forming treatment; (13) In step S3, the silane mixed gas is a mixed gas of silane and an inert gas; (14) In step S3, the silane mixed gas is 20% silane and 80% argon by mass percentage; (15) In step S3, the introduction of the silane mixed gas is carried out at 450-550° C., for example, 550° C.; (16) In step S3, the time for introducing the silane mixed gas is 8 to 12 hours, for example, 10 hours; (17) In step S3, the acetylene mixed gas is 20% acetylene and 80% argon by mass percentage; wherein the ventilation volume of the mixed gas is 4-8 L kg -1 min -1 , for example 5L·kg -1 min -1 ; (18) In step S3, the temperature of the acetylene deposition is 450-550°C, for example, 500°C; (19) In step S3, the acetylene deposition time is 8 to 12 hours, for example, 10 hours.

3. The method for preparing the silicon-carbon negative electrode material according to claim 2, characterized in that: It meets one or more of the following conditions: (1) In step S1, the mixture package is composed of linear phenolic resin, hexamethylenetetramine, carbon nanotubes, defoaming agent and polycarbosilane, Preferably, the mixture consists of 80-120 parts of linear phenolic resin, 4-7 parts of hexamethylenetetramine, 0.05-0.2 parts of carbon nanotubes, 0.05-0.2 parts of defoaming agent and 0.05-0.5 parts of polycarbosilane; (2) In step S1, the rotation speed of the ball milling is 1000-3000 r / min, for example, 2000 r / min; (3) In step S1, the ball milling mixing time is 50 to 80 minutes, for example, 60 minutes; (4) In step S2, the high temperature in the first stage of carbonization causes the polycarbosilane to crosslink; (5) In step S2, the activation medium is carbon dioxide; wherein the gas supply rate of the activation medium carbon dioxide is 1-3 L·kg -1 min -1 , for example 2L·kg -1 min -1 ; (6) In step S2, the activation temperature is 600-1100°C, for example, 550°C; (7) In step S2, the activation time is 1 to 10 hours, for example, 9 hours; (8) In step S3, the silane is SiH4; (9) In step S3, the silane mixed gas is a mixed gas of 20% SiH4 and 80% argon; (10) In step S3, the ventilation volume of the silane mixed gas is 10~20L·kg -1 min -1 , for example 15L·kg -1 min -1 .

4. A silicon-carbon negative electrode material prepared by the preparation method according to any one of claims 1 to 3, characterized in that: It meets one or more of the following conditions: (1) The residual amount of SIC in the silicon-carbon negative electrode material is 0.1-5%; (2) The ratio of the empty volume provided by the mesopores of the silicon-carbon negative electrode material is 12-20%; (3) The mass percentage of the polycarbosilane in the silicon-carbon negative electrode material is 0.09% to 0.4%; (4) The spray-dried particles have a diameter of 7 to 9 μm; (5) The residual carbon rate in the silicon-carbon negative electrode material is 50-70%; (6) The carbonized true density of the silicon-carbon negative electrode material is 2.0-2.8 g / cm³; (7) The particle size (D50) of the silicon-carbon negative electrode material at 20 MPa is 5-9 μm; (8) The BET of the silicon-carbon negative electrode material is 1500~1800 m -2 g; (9) The first cycle expansion of the full battery of the silicon-carbon negative electrode material is 80-98%; (10) The first efficiency of the full battery of the silicon-carbon negative electrode material is 82-90%.

5. The silicon-carbon negative electrode material according to claim 4, characterized in that: It meets one or more of the following conditions: (1) The residual SIC in the silicon-carbon negative electrode material is 0.8% to 3.6%, preferably 1.8% to 3.6%; (2) The spray-dried particles have a diameter of 7.4 to 8.3 μm; (3) The residual carbon rate in the silicon-carbon negative electrode material is 52.4-58.7%; (4) The carbonized true density of the silicon-carbon negative electrode material is 2.69-2.79 g / cm³; (5) The particle size (D50) of the silicon-carbon negative electrode material at 20 MPa is 5.6-8.7 μm, preferably 7.5-8.7 μm; (6) The BET of the silicon-carbon negative electrode material is 1603.9~1780.1 m -2 g; (7) The ratio of the empty volume provided by the mesopores of the silicon-carbon negative electrode material is 12.9-16.7%; (8) The first cycle expansion of the full battery of the silicon-carbon negative electrode material is 89-94%; (9) The first efficiency of the full battery of the silicon-carbon negative electrode material is 82.2~87.8%.

6. A negative electrode slurry, characterized in that: The method comprises the silicon-carbon negative electrode material as claimed in claim 4 or 5, a conductive agent, a binder and a solvent.

7. The negative electrode slurry according to claim 6, characterized in that: It meets one or more of the following conditions: (1) The conductive agent is acetylene black; (2) The binder is polyacrylic acid; (3) The solvent is water, which serves as a dispersant to form a slurry; (4) The solid content of the negative electrode slurry may be 0.1-1 wt %.

8. A negative electrode plate, characterized in that: It is prepared using the negative electrode slurry as claimed in claim 6 or 7, and the preparation method of the negative electrode plate comprises: coating the negative electrode slurry on a current collector and baking.

9. The negative electrode sheet according to claim 8, characterized in that: It meets one or more of the following conditions: (1) The coating is single-sided coating; (2) During the coating, the thickness of the coated active material is 40 μm; (3) During the coating, the coating speed is 40 cm / s; (4) The current collector is a copper foil, and the thickness of the copper foil may be 8-10 μm; (5) The baking temperature is 50°C-130°C; (6) The baking time is 400s.

10. Use of the silicon-carbon negative electrode material according to claim 4 or 5 in a battery, wherein: The application includes the negative electrode sheet as claimed in claim 8 or 9, Preferably, the battery is a lithium-ion battery; The mass fraction of the silicon-carbon negative electrode material in the negative electrode plate is 5-10%, for example 8%.

Citation Information

Cited By

  • Preparation method and application of silicon-carbon negative electrode material

    CN121516853A

  • CVD (Chemical Vapor Deposition) silicon-carbon composite material and preparation method and application thereof

    CN121849906A